The Socratic Method of Instruction: An Experience in Vocabulary Class - Mahmud, Lida Holida; Tryana, Tryana (Universitas Cokroaminoto Palopo, 2024)
The purpose of this study was to establish an environment for critical thinking in a vocabulary course at Universitas Pamulang by implementing Socratic questioning. The use of Socratic questioning aimed to reinforce students' techniques for mastering language and enhance their vocabulary skills. The participants in this study were students enrolled in the first semester of the English Department at Universitas Pamulang. The research followed a Classroom Action research design, which included two cycles of action implementation, class observation, and result analysis. The study utilized observation lists, questionnaires, and a vocabulary test as instruments. The data underwent qualitative analysis, which revealed that the average scores in each cycle demonstrated an upward trend from the pretest to the post-test. However, in the subsequent phase, a fluctuating, steady, and declining score was observed. The students employed Socratic questioning during the vocabulary test. The findings have shown that the use of Socratic inquiry effectively enhances critical thinking among students and facilitates vocabulary learning by prompting reevaluation. Consequently, it motivates students to engage in reflective thinking and provide precise answers.